Nitrogen Deposition to an Alberta Bog as Measured with Mixed-bed Ion Exchange Resin Tube Collectors, 2011-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). Resin tubes filled with mixed-bed ion exchange resin were swapped in and out at each collection/deployment date (mid-May and mid-October of each year). Upon collection, resins were extracted with 1M KI and analyzed for inorganic N concentrations. Deposition of NH 4 + -N, NO 3 - -N, and DIN averaged 187 ± 11, 237 ± 13, and 426 ± 19 μg m -2 da -1 , corresponding to 0.68 ± 0.04, 0.87 ± 0.05, and 1.55 ± 0.07 kg N ha -1 yr -1 , with no significant differences between open and throughfall collectors for any of the three measured parameters (p >= 0.63). Deposition of NH 4 + -N was significantly higher during the growing season (averaging 240 μg m -2 da -1 ) than during the winter months (averaging 121 μg m -2 da -1 ) (p = 0.0004), while NO 3 - -N and DIN deposition did not differ significantly between winter and summer (p = 0.06 and 0.13, respectively).